1991
DOI: 10.1302/0301-620x.73b1.1991771
|View full text |Cite
|
Sign up to set email alerts
|

Micromotion of cemented and uncemented femoral components

Abstract: We evaluated the initial stability of cemented and uncemented femoral components within the femoral canals of cadaver femurs during simulated single limb stance and stair climbing. Both types were very stable in simulated single limb stance (maximum micromotion of 42 microns for cemented and 30 microns for uncemented components). However, in simulated stair climbing, the cemented components were much more stable than the uncemented components (76 microns as against 280 microns). There was also greater variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
0
8

Year Published

1993
1993
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(98 citation statements)
references
References 0 publications
12
77
0
8
Order By: Relevance
“…However, proximal bone resorption due to distal fixation and proximal stress shielding has caused concerns and this has led to newer designs with a porous-coating applied only to the proximal metaphyseal part of the stem [13,14,31,37]. Femoral stem micro-motion studies have emphasized the importance of metaphyseal fit in reducing torsional motion [2,4,15] and enable bone ingrowth [5,38]. Likewise, inadequate canal filling has been considered to be the main cause for stem failures [7,9,30,31], and in the series of Kim and Kim [24,25,26] a poor initial stem "fit-and-fill" was associated with thigh pain and component loosening.…”
Section: Introductionmentioning
confidence: 99%
“…However, proximal bone resorption due to distal fixation and proximal stress shielding has caused concerns and this has led to newer designs with a porous-coating applied only to the proximal metaphyseal part of the stem [13,14,31,37]. Femoral stem micro-motion studies have emphasized the importance of metaphyseal fit in reducing torsional motion [2,4,15] and enable bone ingrowth [5,38]. Likewise, inadequate canal filling has been considered to be the main cause for stem failures [7,9,30,31], and in the series of Kim and Kim [24,25,26] a poor initial stem "fit-and-fill" was associated with thigh pain and component loosening.…”
Section: Introductionmentioning
confidence: 99%
“…It is not quite certain, what is the micromotion at the boneingrowth surface area preventing bone ingrowth. In simulated stair climbing micromotion of cementless implants it is up to 280 ÎŒm (Burke et al 1991) which is close to 100-400 ÎŒm pore size commonly used in the porous coated implants still allowing bone ingrowth. The best implant-bone contact (bone ingrowth) is achieved in contact with compact, cortical bone characterized by Haversian channels.…”
Section: Physiological Fixation Of Uncemented Implantsmentioning
confidence: 63%
“…Burke and colleagues reported vertical motions up to 30 (cementless stems) and 42 Ă­m (cemented stems) under vertical loading of 445 N, but adding torsional loading increased these to 76 (cemented ) and 280 Ă­m (cementless) [26 ]. Walker et al [24] reported micromotions of 10-50 Ă­m, the smallest movements for cemented stems.…”
Section: Discussionmentioning
confidence: 98%